Automatic vegetation identification and building detection from a single nadir aerial image - Shorter, Nicholas; Kasparis, Takis (My University, 2009)
A novel, automatic tertiary classifier is proposed for identifying vegetation, building and non-building objects from a single nadir aerial image. The method is unsupervised, that is, no parameter adjustment is done during the algorithm's execution. The only assumption the algorithm makes about the building structures is that they have convex rooftop sections. Results are provided for two different actual data sets. © 2009 by the authors; licensee Molecular Diversity Preservation International, Basel, Switzerland.
Keywords: Building detection; Color invariants; Nadir aerial image; Vegetation identification